Adaptation Strategies of the U.S. Companies to the Digitalization of Production - V. P. Bauer; G. L. Podvoisky; N. E. Kotova (Мир новой экономики)
The article considers one of the little-studied scientific problems — the problem of adaptation to digitalization in the sphere of production. This problem is investigated by the authors on the example of American companies. The researchers set themselves the task of analyzing various aspects of this problem — to identify the features and stages of adaptation of American companies in the implementation of digitalization in the field of production. The analysis of various scientific, analytical and expert sources allowed the authors to formulate not only the peculiarities of the processes of adaptation of American companies to digitalization in the field of production but also to identify the logic of the transition to the main levels of this adaptation from the lowest to the highest. The novelty and complexity of the problem of adaptation of the company in the process of informatization, according to the authors, significantly increases the role and responsibility of company managers, their ability to accept and actively contribute to new management practices. The study conducted by the authors showed that in the process of developing a strategy for the adaptation of American companies to digitalization in the field of production, various aspects should be taken into account, new technologies and management practices should be developed. The analysis of the problem allowed the authors to make significant progress in understanding the complexity of the adaptation processes of companies that start the process of digitalization.